2023
DOI: 10.1002/cpt.3084
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Use of Fluoroquinolones and Risk of Mitral or Aortic Valve Regurgitation: A Nationwide Cohort Study

Yaa‐Hui Dong,
Jiun‐Ling Wang,
Chia‐Hsuin Chang
et al.

Abstract: Biological plausibility suggests that fluoroquinolones may lead to mitral valve regurgitation or aortic valve regurgitation (MR/AR) through a collagen degradation pathway. However, available real‐world studies were limited and yielded inconsistent findings. We estimated the risk of MR/AR associated with fluoroquinolones compared with other antibiotics with similar indications in a population‐based cohort study. We identified adult patients who initiated fluoroquinolones or comparison antibiotics from the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…A recent nationwide cohort study in Taiwan found no link between FQs and an increased risk of mitral or aortic regurgitation [ 12 ]. They employed an active comparative study design, comparing FQs with amoxicillin/clavulanate among different individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent nationwide cohort study in Taiwan found no link between FQs and an increased risk of mitral or aortic regurgitation [ 12 ]. They employed an active comparative study design, comparing FQs with amoxicillin/clavulanate among different individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Other commonly prescribed antibiotics were selected as the negative control exposures, including amoxicillin, trimethoprim and sulfamethoxazole (TMP/SMX), amoxicillin clavulanate (AMC) and ampicillin sulbactam (ASB), and the second-generation drug cephalosporin. These antibiotics were chosen because their indications are generally similar to those of fluoroquinolones, according to treatment guidelines in Taiwan and other regions of Asia [ 12 ]. The definition of exposure was defined as a prescription ≥3 days in the outpatient department.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation